Analisis Perubahan Volume pada Timbunan Tanah Lempung Berdasarkan Nilai Batas Susut (SNI 3422:2008) - Yudhyantoro, Yus; Prayoga, Andri; Maimunah, Maimunah (University of Muhammadiyah Aceh, 2022)
Sedimentation has continuously resulted in siltation of the port of Pelabuhan Perikanan Samudera (PPS) Lampulo located in Kuta Alam District, Banda Aceh City. The dredged soil collected outside the port area visually indicates clay soil. In addition to the low bearing capacity and high plasticity, the effect of water on clay is high swelling and shrinkage. One of the prominent behaviors that cause major damage to structures built on clay is associated with volume decrease i.e., shrinkage in saturated compressible clay soil when water get evaporated. Shrinkage in clay will result in volume changes. The purpose of this research is to calculate the volume changes in mound of clay soil based on shrinkage limit values using SNI 3422:2008. The soil sample used is an undisturbed sample (UDS) originating from the dredging area of the port of PPS Lampulo. The test consists of water content, specific gravity, liquid limit, plastic limit, shrinkage limit and grain size distribution using the SNI method. Based on the results of the index properties test, according to AASHTO the soil sample belongs to group A-7-5 which means it is a clay soil with a GI value greater than 20, so it is considered poor as a subgrade soil. According to USCS, the soil belongs to the CH classification, which means clay soil with high plasticity, so it has a large potential for expansion and shrinkage. Based on SNI 3422:2008, the average shrinkage limit (SL) is 21.21%, the average shrinkage ratio (R) is 2.27% and the average linear shrinkage (LS) is 9.65%. With an average volume change (VC) value of 35.59%, the shrinkage volume of soil embankment of the dredging area of the port of PPS Lampulo is 32,438.85 m3 compared to its initial volume (91,145.97 m3). Therefore, the shrinkage limit is an important parameter for calculating the volume shrinkage in mound of soil due to the soil type is clay with high plasticity.